The Other Side of the Story: Knowledge Transfer and Advice-Giving in a Drug Subculture. Issue 5 (4th May 2017) - Marin, Alexandra C.; Kelly, Brian C.; Parsons, Jeffrey T.
ABSTRACT: Widely used as a framework for understanding drug use initiation, social learning theory has lacked considerations of peer effects from the standpoint of the experienced user and applications to hard drugs. This study aims to extend social learning theory by examining the advice an experienced drug user would give a younger friend or relative expressing desire to experiment with club drugs. Forty qualitative interviews with club drugs users were analyzed. The experienced user's own initiation, previous experiences, and risk perceptions are important in how advice is constructed. We discovered variations in advice-giving for friends and family members that may be based on considerations of age appropriateness.